2008
DOI: 10.20886/jphh.2008.26.2.117-128
|View full text |Cite
|
Sign up to set email alerts
|

KARAKTERISTIK KAYU MUDA PADA MANGIUM (Acacia mangium Willd.) DAN KUALITAS PENGERINGANNYA

Abstract: Recently, the availability of wood species from natural forests has run limited and scarce. Consequently, fulfilling public demand of wood is met in part by woods from plantation forest. The problem with the plantation forest is that its woods contain relatively high juvenile wood portions due to the felling or harvesting at relatively younger tree ages (with shorter rotation) than those from natural forest trees.In wood processing the presence of juvenile wood often causes problems with its corresponding prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…Recent studies by Hamdan et al [42] and Chen et al [43] have observed that vessel diameter, fiber length, and fiber wall thickness significantly affected the density and mechanical properties of wood. In addition, juvenile and mature wood played a crucial role in determining the anatomical characteristics that will impact the wood quality [17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Anatomical Characteristics Affecting Wood Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies by Hamdan et al [42] and Chen et al [43] have observed that vessel diameter, fiber length, and fiber wall thickness significantly affected the density and mechanical properties of wood. In addition, juvenile and mature wood played a crucial role in determining the anatomical characteristics that will impact the wood quality [17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Anatomical Characteristics Affecting Wood Qualitymentioning
confidence: 99%
“…As described by Kozlowski [17], Tsoumis [18], and Moore and Cown [19], juvenile wood forms near the pith and exhibits considerable changes in cell characteristics such as shorter cells, thinner cell walls, narrower cell diameter, and a higher microfibril angle. Therefore, juvenile wood possesses poorer physical [20,21] and mechanical properties than mature wood [22][23][24][25], as well as reduced natural durability [26] and diminished drying quality [27,28]. Therefore, more juvenile wood can significantly impact the overall wood quality [29].…”
Section: Introductionmentioning
confidence: 99%
“…Kayu juvenil masih mengalami perubahan sifat pada dimensi serat, kerapatan, dan sifat lainnya. Beberapa penelitian mengenai kayu juvenil di Indonesia diantaranya pada kayu mangium (Lukmandaru, 2012;Rulliaty, 2008), sengon dan jabon (Darmawan, Nandika, Rahayu, & Fournier, 2013), serta samama (Cahyono et al, 2015). Semua penelitian tersebut menyatakan bahwa sampai umur 6 tahun, pada pohon yang diteliti masih terdiri dari kayu juvenil.…”
Section: Pendahuluanunclassified
“…Hal ini dikaitkan dengan pernyataan Fengel & Wegener, (1995) kuat, makanya kadar lignin umur 2 sampai 4 tahun lebih tinggi dibandingkan dengan kadar lignin umur 1 tahun. Bila dibandingkan dengan kayu juvenil pada umumnya, sebagaimana dilaporkan Rulliaty (2008), karakteristik dimensi serat kayu juvenil pada awal pertumbuhan lebih pendek dan dinding sel lebih tipis. Hal ini diduga walaupun dinding sel tipis namun rendahnya persentase lignin menjadikan kadar selulosa lebih tinggi pada umur 1 tahun.…”
Section: Tabel 1 Data Pohon Yang Digunakan Dalam Penelitianunclassified
See 1 more Smart Citation